2020
DOI: 10.1002/gcc.22834
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of NanoString nCounter FusionPlex profiling in soft tissue tumors

Abstract: Diagnostic histopathology of soft tissue tumors can be troublesome as many entities are quite rare and have overlapping morphologic features. Many soft tissue tumors harbor tumor‐defining gene translocations, which may provide an important ancillary tool for tumor diagnosis. The NanoString nCounter platform enables multiplex detection of pre‐defined gene fusion transcripts in formalin‐fixed and paraffin‐embedded tissue. A cohort of 104 soft tissue tumors representing 20 different histological types was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The nCounter platform is increasingly being used for fusion detection in NSCLC and other types of tumors [ 18 , 19 , 20 , 21 ]. However, there is only one report in the literature describing the performance of nCounter in cytological samples, and MET alterations were not tested [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nCounter platform is increasingly being used for fusion detection in NSCLC and other types of tumors [ 18 , 19 , 20 , 21 ]. However, there is only one report in the literature describing the performance of nCounter in cytological samples, and MET alterations were not tested [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows for fusion detection in sarcoma subtypes with high variability in the partner genes or breakpoints for which fusion spanning probes are not effective. The assay by Chang et al was later independently evaluated and found to have 85% sensitivity and 100% specificity in a set of 104 soft tissue tumors 85,87 . Using a similar premise, Sheth et al later developed an assay for the 22 most common pediatric sarcoma fusion transcripts, which proved to be 100% concordant with the RT‐PCR results used to select the 45 tested tumor samples 88 …”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…sensitivity and 100% specificity in a set of 104 soft tissue tumors 85,87. Using a similar premise, Sheth et al later developed an assay for the 22 most common pediatric sarcoma fusion transcripts, which proved to be 100% concordant with the RT-PCR results used to select the 45 tested tumor samples 88.…”
mentioning
confidence: 99%
“…NGS-based approaches are recommended for classifying small round cell sarcomas where a diagnosis consistent with ES cannot be made following classic immunohistochemistry, FISH, or RT-PCR. Several NGS assays, such as the Archer FusionPlex sarcoma assay, or different NanoString assays are available, but cost is still an issue [ 36 , 37 , 38 , 39 ]. Although CD99 is an extremely sensitive marker for ES, CD99 staining is very unspecific as it stains positive in a variety of other tumors [ 40 ].…”
Section: Molecular Diagnosticsmentioning
confidence: 99%